Comparison of Diffusion-Weighted Imaging in the Human Brain Using Readout-Segmented EPI and PROPELLER Turbo Spin Echo With Single-Shot EPI at 7 T MRI. Issue 7 (July 2016) - Kida, Ikuhiro; Ueguchi, Takashi; Matsuoka, Yuichiro; Zhou, Kun; Stemmer, Alto; Porter, David
Abstract : Objectives: The purpose of the present study was to compare periodically rotated overlapping parallel lines with enhanced reconstruction–type turbo spin echo diffusion-weighted imaging (pTSE-DWI) and readout-segmented echo planar imaging (rsEPI-DWI) with single-shot echo planar imaging (ssEPI-DWI) in a 7 T human MR system. We evaluated the signal-to-noise ratio (SNR), image distortion, and apparent diffusion coefficient values in the human brain. Materials and Methods: Six healthy volunteers were included in this study. The study protocol was approved by our institutional review board. All measurements were performed at 7 T using pTSE-DWI, rsEPI-DWI, and ssEPI-DWI sequences. The spatial resolution was 1.2 × 1.2 mm 2 in-plane with a 3-mm slice thickness. Signal-to-noise ratio was measured using 2 scans. Results: The ssEPI-DWI sequence showed significant image blurring, whereas pTSE-DWI and rsEPI-DWI sequences demonstrated high image quality with low geometrical distortion compared with reference T2-weighted, turbo spin echo images. Signal loss in ventral regions near the air-filled paranasal sinus/nasal cavity was found in ssEPI-DWI and rsEPI-DWI but not pTSE-DWI. The apparent diffusion coefficient values for ssEPI-DWI were 824 ± 17 × 10 −6 and 749 ± 25 × 10 −6 mm 2 /s in the gray matter and white matter, respectively; the values obtained for pTSE-DWI were 798 ± 21 × 10 −6 and 865 ± 40 × 10 −6 mm 2 /s; and the values obtained for rsEPI-DWI were 730 ± 12 × 10 −6 and 722 ± 25 × 10 −6 mm 2 /s. The pTSE-DWI images showed no additional distortion comparison to the T2-weighted images, but had a lower SNR than ssEPI-DWI and rsEPI-DWI. The rsEPI-DWI sequence provided high-quality images with minor distortion and a similar SNR to ssEPI-DWI. Conclusions: Our results suggest that the benefits of the rsEPI-DWI and pTSE-DWI sequences, in terms of SNR, image quality, and image distortion, appear to outweigh those of ssEPI-DWI. Thus, pTSE-DWI and rsEPI-DWI at 7 T have great potential use for clinical diagnoses. However, it is noteworthy that both sequences are limited by the scan time required. In addition, pTSE-DWI has limitations on the number of slices due to specific absorption rate. Overall, rsEPI-DWI is a favorable imaging sequence, taking into account the SNR and image quality at 7 T.